Effectiveness of Formative Evaluation in Improving Students Understanding and Character - Wungo, Jefrianus; Oktavianti, Nelci; Mulyani, Sri (Scriptura Indonesia, 2025)
This article examines the effectiveness of formative evaluation in improving understanding and human development. Formative evaluation conducted during learning is a feedback to help students improve their weaknesses before the final evaluation. This evaluation not only assesses learning outcomes, but also identifies difficulties faced by students, allowing teachers to change teaching methods to support individual student needs. Formative evaluation also helps improve students' critical thinking skills, engagement and understanding of the subject matter. In addition, this review plays an important role in building student character, including increasing motivation, self-confidence and responsibility for the learning process. Thus, formative evaluation becomes a useful tool in building an inclusive learning environment and focusing on student growth.